2007
DOI: 10.1155/2007/23624
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and O2 Enhanced MRI of the Pathologic Lung: Findings in Emphysema, Fibrosis, and Cystic Fibrosis

Abstract: Purpose: beyond the pure morphological visual representation, MR imaging offers the possibility to quantify parameters in the healthy, as well as, in pathologic lung parenchyma. Gas exchange is the primary function of the lung and the transport of oxygen plays a key role in pulmonary physiology and pathophysiology. The purpose of this review is to present a short overview of the relaxation mechanisms of the lung and the current technical concepts of T1 mapping and methods of oxygen enhanced MR imaging. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…The entire-lung median PO 2max l showed slightly better correlations with PFT parameters than the enhancing-region median PO 2max l . Similar correlations of OE-MRI readouts with FEV 1 %predicted, FVC%predicted, FEV 1 /FVC ratio and MMEF%predicted have been demonstrated in asthmatics and patients with other lung diseases [13,15,[19][20][21], while the correlations with the airway resistance indices of sR tot and sR eff are to our knowledge the first reported. In a previous asthma OE-MRI study, Ohno et al reported significant but much weaker correlations between the mean signal enhancement ratio and FEV 1 (r = 0.55, P < 0.05) and the average forced expiratory flow between 25% point and 75% point of FVC (FEF 25%-75% , r = 0.55, P < 0.05) [21].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The entire-lung median PO 2max l showed slightly better correlations with PFT parameters than the enhancing-region median PO 2max l . Similar correlations of OE-MRI readouts with FEV 1 %predicted, FVC%predicted, FEV 1 /FVC ratio and MMEF%predicted have been demonstrated in asthmatics and patients with other lung diseases [13,15,[19][20][21], while the correlations with the airway resistance indices of sR tot and sR eff are to our knowledge the first reported. In a previous asthma OE-MRI study, Ohno et al reported significant but much weaker correlations between the mean signal enhancement ratio and FEV 1 (r = 0.55, P < 0.05) and the average forced expiratory flow between 25% point and 75% point of FVC (FEF 25%-75% , r = 0.55, P < 0.05) [21].…”
Section: Discussionsupporting
confidence: 79%
“…Dynamic oxygen-enhanced (OE-) MRI can provide spatial and temporal information on regional delivery and uptake of O 2 in the lung by using 16 O 2 as a contrast agent [10][11][12][13]. The paramagnetic O 2 molecules dissolve in the tissue water and blood plasma within the lung and increase the lung spin-lattice relaxation rate (R 1 ) in proportion to dissolved O 2 concentration [11] and thus the local O 2 partial pressure (PO 2 ) [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, modulation of T1 values seen in parenchymal lesions may complicate the variation. For example, it was reported that the T1 values of the lung were shorter in pulmonary emphysema (33) and fibrosis (34) than in normal lungs. Moreover, inversion-recovery HASTE is time consuming, and difficult to assess oxygen-enhancement within whole lung.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperpolarized gases such as helium or xenon are used for ventilation imaging with high resolution and SNR at a few specialized centers . Oxygen‐enhanced MRI is a cheaper alternative, but low SNR and long acquisition times limit its broader utilization …”
Section: Introductionmentioning
confidence: 99%